Effects of family participatory dignity therapy on the psychological well-being and family function of patients with haematologic malignancies and their family caregivers: A randomised controlled trial. (June 2021) - Wang, Chunfeng; Chen, Jingyi; Wang, Ying; Xu, Wenkui; Xie, Mengting; Wu, Yong; Hu, Rong
Abstract: Background: Strong family ties appear to buffer patient's and family members' difficult experiences during life and health crises. The family participatory dignity therapy programme, a patient-family-centred psychological intervention, was developed based on dignity therapy and performed by one therapist in the form of interview according to a specific question prompt. Objectives: This study aimed to confirm the efficacy of the family participatory dignity therapy programme in improving the psychological well-being and family cohesion and adaptability of patients with haematologic malignancies and their family caregivers. Design: A single-blinded, two-arm parallel group, randomised controlled trial was conducted. Setting(s): and Participants: Participants were patient-family caregiver dyads recruited from Fujian Medical University Union Hospital from March to September 2019. Methods: A total of 68 eligible dyads agreed to participate and were randomly assigned to the intervention group ( n  = 33) or control group receiving usual care ( n  = 35). Each pair of patient-family dyads in the intervention group received two or three interviews (each interview approximately lasting 45 to 60 min) performed by one therapist according to a specific question prompt containing 10 questions for patients and 10 corresponding questions for their family caregivers. To evaluate the effects of the intervention, we assessed patients' hope, spiritual well-being, and family cohesion and adaptability, as well as their family caregivers' depression, anxiety, and family cohesion and adaptability at baseline (T0), 1 week (T1), 4 weeks (T2), and 8 weeks post-intervention (T3) and compared the scores between the groups. A two-way repeated-measures analysis of variance was conducted to examine the effects of time, group, and their interaction. Results: For patients, there was a significant difference in hope ( p  = 0.001), spiritual well-being ( p  = 0.002), and family cohesion ( p <0.001) and adaptability ( p <0.001) between the intervention and control groups. The difference over time was also significant in family cohesion ( p  = 0.018) and adaptability ( p  = 0.003). The interaction effects were significant for hope ( p  = 0.034), spiritual well-being ( p <0.001), and family cohesion ( p <0.001) and adaptability ( p <0.001). For family caregivers, there was a significant difference in anxiety ( p  = 0.037), depression ( p  = 0.001), and family adaptability ( p  = 0.036) between the intervention and control groups. Within groups, a significant difference in family adaptability ( p  = 0.012) was found. Moreover, the interaction effects were significant on anxiety ( p  = 0.001) and family cohesion ( p  = 0.038). Conclusions: The family participatory dignity therapy programme showed a positive effect on promoting patients' hope, spiritual well-being, and family cohesion and adaptability; amongst family caregivers, it decreased anxiety and depression, and enhanced family cohesion and adaptability. Registration number: ChiCTR1900021433 Tweetable abstract: The family participatory dignity therapy programme promoted patients' hope, spiritual well-being, and family cohesion and adaptability, decreased their family caregivers' anxiety and depression, and enhanced the caregivers' family cohesion and adaptability.